A systematic review of qualitative research on the role of ICTs in sustainable livelihood - Zaremohzzabieh, Zeinab; Abu Samah, Bahaman; Omar, Siti Zobidah; Bolong, Jusang; Mohamed Shaffril, Hayrol Azril (Medwell Journals, 2014)
In the recent past, the role of Information Communication Technologies (ICTs) in promoting socio-economic development and sustainable livelihoods has become the subject of heated debate. Nevertheless, an insufficient number of studies have systematically reviewed the growing influence of ICTs. In the present study, a systematic review is conducted to evaluate and examine qualitative studies that have explored the role of ICTs in contributing to sustainable livelihoods. Researchers performed a systematic literature review of studies written in English and published between January, 2007 and April, 2014. Inclusion and exclusion principles were employed to identify studies of any qualitative design that examined the concept of sustainable livelihoods through the lens of accumulation of assets in order to evaluate the purposes for which ICTs are utilized and also to review the impact that ICTs have had on various aspects of life. Researchers screened and retrieved all titles and abstracts and potentially relevant studies to establish whether the study met the inclusion criteria, yielding a total of 15 primary studies. Researchers then extracted the precise findings of studies that were relevant to the review through ATLAS.ti7 software in order to allow us to code the key themes, sub-themes and inter-relationships. The results of the review reveal that ICTs have certain influences on sustainable livelihoods and that this influence applies to human, social, financial, physical and natural assets. This review has the potential to address managerial problems by creating a reliable knowledge base that accumulates findings from the selected studies and highlights opportunities for further research.